Serious Efforts at Bias Reduction : The Effects of Digital Games and Avatar Customization on Three Cognitive Biases - Shaw, Adrienne and Kenski, Kate and Stromer-Galley, Jennifer and Mikeal Martey, Rosa and Clegg, Benjamin A. and Lewis, Joanna E. and Folkestad, James E. and Strzalkowski, Tomek (Journal of Media Psychology, 2018)
Abstract. As research on serious games continues to grow, we investigate the efficacy of digital games to train enhanced decision making through understanding cognitive biases. This study investigates the ability of a 30-minute digital game as compared with a 30-minute video to teach people how to recognize and mitigate three cognitive biases: fundamental attribution error, confirmation bias, and bias blind spot. We investigate the effects of character customization on learning outcomes as compared with an assigned character. We use interviews to understand the qualitative differences between the conditions. Experimental results suggest that the game was more effective at teaching and mitigating cognitive biases than was the training video. Although interviews suggest players liked avatar customization, results of the experiment indicate that avatar customization had no significant effect on learning outcomes. This research provides information future designers can use to choose the best medium and affordances for the most effective learning outcomes on cognitive processes.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAyNy8xODY0LTExMDUvYTAwMDE3NA